Actualización sobre el manejo diagnóstico y terapéutico de la osteomielitis. - Bastidas Parra, Dayana Stephanie (2024)
Osteomyelitis is an infectious process of the bone that affects the health status of patients, its causes can be multiple; the diagnosis and treatment are complex, reason why it continues generating functional disability and affect the life quality. The objective of this research was to carry out a bibliographic review to obtain updated information related to the diagnostic and therapeutic management of osteomyelitis. For this, a basic study carried out a documentary, descriptive and cross-sectional design consisting of a nonsystematic bibliographic review that mainly included documents published in the last 5 years. The universe consisted of a total of 86 documents; a total of 35 were included as part of the research sample. Information is available in regional databases such as Latindex, Lilacs, Scielo and Redalyc, and high-impact databases such as Scopus, PubMed and Ice Web. Boolean operators and health descriptors were used. The main results includes the description of the clinical, pathophysiological, epidemiological, imaging and laboratory elements that enable clinical suspicion and definitive diagnosis of osteomyelitis; the main pharmacological groups used as part of the therapeutic schemes for this disease and the correlation of the pathophysiological elements with the pharmacological groups that are traditionally used. Is concluded that osteomyelitis continues being a health problem that, although its main diagnostic and therapeutic elements are known, continues representing a challenge for health professionals